Reżyserskie szlify. Władysław Ślesicki w Szkole Filmowej (1950-1955) - Pławuszewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Movie Director Exercise. Władysław Ślesicki and a Film School (1950–1955) The article discusses Władysław Ślesicki’s studies at the Lodz Film School (1950–1955). The years he spent at Film Directing Department were fruitful not only because of a few worth-while writings, but also due to some of his first directing experiences. Ślesicki was an assistant on the set of Kazimierz Karabasz’s school films, but he also directed his own (debut) short movies (the short feature Kawaler Kubiak; the short documentary Jedzie tabor). The claim is also made that these early works foreshadow his unique cinematic style, which Władysław Ślesicki developed especially within the documentary genre and which gave him a lasting place in the history of Polish cinema.